Passive Hemagglutination Test for Bovine Chlamydial Abortion - Belden, E. L. (1973)
Purified chlamydial elementary bodies were subjected to sonic lysis to produce soluble antigen for passive hemagglutination (PHA). PHA was more sensitive than complement fixation (CF) in detecting antibody in hyperimmunized rabbits, lambs, and calves. Both CF and PHA tests were used to monitor antibody responses in experimentally infected pregnant cows. All animals responded with rises in titers after experimental infection. Titers declined and then increased a second time near the time of abortion. PHA titers were considerably higher than CF titers.